A Correlation Between Mass Media Communication and Foreign Investments in India - Tewari, Ruchi; Pathak, Taral (Prabandhan: Indian Journal of Management, 2015)
Background and Purpose: India opened its doors to globalization in 1991, and the reference point of this change through globalization has been the United States of America (USA), which champions the cause of a free economy. The current study attempted to explore the relevance and importance that globalization has brought to India through mapping the shifting pattern of mass media coverage of India by the foreign media and parallelly marking the shifting patterns in investments made by foreign financial institutions in India over the last decade and a half. Design/Methodology/Approach: Top 25 news articles about India reported by The New York Times (NYT), every year, over a span two decades (1991-2010) were taken from the NYT website. The 500 news reports were filtered and news falling in the category of "Business and Personal Finance" (BPF) were used for content analysis and categorized into three broad types - good, bad, or neutral. Similarly, the investments made by foreign institutions (FII) in India were noted over the same period to explore a correlation between the BPF media reports and the investments made by FIIs in India. Since media reports do not often have an immediate impact, a lag effect of 1 year was checked. The data was statistically validated. Findings: The findings indicate an exponential rise in the number of news items which NYT carried about India over a period of two decades. There was a change in the category of news coverage from 'Arts and Culture' to 'Politics and Business'. The type of news reports changed from neutral to positive and the news reporting was more visually aided with photographs and pictures. A similar pattern was noticed in the foreign investments by institutions, which grew over a period of time. This clearly indicated the existence of a relationship between positive news coverage by independent media and a rise in the amount of investments made by foreign institutions. Research Limitations/Implications: The study was limited to establishing a relationship between media representation and investments by foreign institutions, but the direction and the intensity of the relationship was not established. A lag effect of 1 year was considered. Originality/Value: Observations and comments about India's changing position as a potential economic power and the positive prospect for investments were made, which were empirically validated by the study. The study also brought out one of the factors which positively impacted investments in a developing nation like India.